Tradisi Remaja Menikah Usia Dini di Kecamatan Seulimum Kabupaten Aceh Besar Provinsi Aceh - Abdi, Abdul Wahab (Pusat Kajian Demografi, Etnografi dan Transformasi Sosial, 2024)
Abstract. The high number of adolescent marriages at an early age does not matter to the community in Seulimum sub-district, although the government has limited the minimum age of women and men to marry in Indonesia, the age limit is not a primary consideration of adolescents located in Seulimum Sub- Aceh Besar District. The purpose of this study is to detect the main factors that cause high rates of early marriage in adolescents in the District of Seulimum Aceh Besar District. The research used descriptive analysis method percentage for data processing. The population in this study amounted to 205 souls and the sample of 40 people. Data collection techniques are questionnaires that are closed and observation. Based on data processing obtained, less agree (20.5%), disagree (10.5%), so it can be concluded that most (69%) of seulimum subdistrict support the decision to marry at a young age, Islamic religious culture in society. Also, as a result of non-formal education of adolescent girls in traditional pesantren in the community, coupled with adolescent girls is not required to continue education to a higher level. In the end, make other teenage girls to follow peers who have been married at an early age in the surrounding community.